Location‐based coverage and capacity analysis of a two tier HetNet. Issue 7 (11th April 2017) - Pervez, Muhammad Mussawer; Abbas, Ziaul Haq; Muhammad, Fazal; Jiao, Lei
Abstract : Stochastic geometry tool is an accurate and tractable approach to analyse the performance characteristics of heterogeneous networks (HetNets) with unplanned deployment of base stations (BSs). In this study, the authors analyse the downlink coverage and capacity by taking into account the separation between the macro BS (MBS) and small BSs (SBSs) in a HetNet. MBSs, SBSs, and users are spatially distributed as independent Poisson point processes. The whole space is divided into inner and outer subspaces around the MBSs and a typical user is assumed to be in outer subspace. Analysis on the typical user in the outer subspace incorporates the effect of distance of SBSs from MBS. They derive the expressions for the coverage probability of an outer subspace typical user from SBS and MBS. They also derive the expressions for rate coverage of an outer subspace typical user from SBS and MBS. These metrics are analysed with varying inner subspace radius to incorporate the effect of BSs separation. Simulation results show that SBSs away from MBS in the coverage region of MBS provide good performance to their associated users in terms of coverage probability and rate coverage.